2005
DOI: 10.1038/sj.ijir.3901352
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of sexual dysfunction among young adult married women in rural China: a population-based study

Abstract: The study investigates prevalence of sexual dysfunction (SD), sexual satisfaction and their correlates in the rural female population in China. An anonymous cross-sectional study was carried out in a random sample of 1178 married of age 20-39 years in Dengfeng County, Henan, China. The prevalence of having at least one SD was 43 and 38% of the respondents were satisfied with their sexual life; 64.0% thought that sex was not important to them; and 85.7% believed that they do not have adequate sex-related knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 21 publications
4
40
2
1
Order By: Relevance
“…It is equally difficult to see how masturbation develops sexual interests, when greater masturbation frequency is so often associated with impaired sexual function in men (Brody & Costa, 2009;Das, Parish, & Laumann, 2009;Gerressu, Mercer, Graham, Wellings, & Johnson, 2008;Lau, Wang, Cheng, & Yang, 2005;Nutter & Condron, 1985) and women (Brody & Costa, 2009;Das et al, 2009;Gerressu et al, 2008;Lau, Cheng, Wang, & Yang, 2006;Shaeer, Shaeer, & Shaeer, 2012;Weiss & Brody, 2009). Greater masturbation frequency is also associated with more dissatisfaction with relationships and less love for partners (Brody, 2010;Brody & Costa, 2009).…”
mentioning
confidence: 99%
“…It is equally difficult to see how masturbation develops sexual interests, when greater masturbation frequency is so often associated with impaired sexual function in men (Brody & Costa, 2009;Das, Parish, & Laumann, 2009;Gerressu, Mercer, Graham, Wellings, & Johnson, 2008;Lau, Wang, Cheng, & Yang, 2005;Nutter & Condron, 1985) and women (Brody & Costa, 2009;Das et al, 2009;Gerressu et al, 2008;Lau, Cheng, Wang, & Yang, 2006;Shaeer, Shaeer, & Shaeer, 2012;Weiss & Brody, 2009). Greater masturbation frequency is also associated with more dissatisfaction with relationships and less love for partners (Brody, 2010;Brody & Costa, 2009).…”
mentioning
confidence: 99%
“…A study of married women found that PVI was related to both marital and sexual satisfaction, cunnilingus was unrelated and masturbating the male partner until orgasm was associated with both poorer marital and sexual satisfaction (Hurlbert & Apt, 1994). In a national probability British subsample (Gerressu et al, 2008) and in a Chinese subsample (Das et al, 2009), female masturbation was associated with a series of sexual difficulties, which was confirmed in a Chinese random sample (Lau et al, 2006) and among Arabic women (Shaeer et al, 2012). Also, as discussed above, women who never had PVI orgasm have more difficulties during childbirth (Baxter, 1974) and, as will be discussed below, PVI frequency was found to be protective against breast cancer, but condom use or coitus interruptus were associated with increased risk (Gjorgov, 1978(Gjorgov, , 1998Le, Bachelot, & Hill, 1989;Vessey, Baron, Doll, McPherson, & Yeates, 1983).…”
Section: Independent Confirmationsmentioning
confidence: 71%
“…Congruent with the view that vaginal orgasm has an adaptive role of reinforcing desire for PVI, vaginal orgasm and PVI frequency are consistently associated with sexual satisfaction, relationship satisfaction, greater sexual desire and less risk of sexual dysfunction (Brody, 2007b;Brody & Weiss, 2011b;Costa & Brody, 2007;Fugl-Meyer, Oberg, Lundberg, Lewin, & Fugl-Meyer, 2006;Nutter & Condron, 1983;Philippsohn & Hartmann, 2009;Tao & Brody, 2011;Weiss & Brody, 2009a). In contrast, other sexual behaviors are frequently uncorrelated or correlated with more sexual difficulties (Brody & Costa, 2009b;Brody & Weiss, 2011a;Costa & Brody, 2007;Das, Parish, & Laumann, 2009;Gerressu, Mercer, Graham, Wellings, & Johnson, 2008;Lau, Cheng, Wang, & Yang, 2006;Nutter & Condron, 1983;Philippsohn & Hartmann, 2009;Shaeer, Shaeer, & Shaeer, 2012;Tao & Brody, 2011;Weiss & Brody, 2009a). Although Prause ignores this literature in her review concluding that orgasm has no primary role in rewarding women's sexual behavior, her own data seemingly conform to the pattern: women who considered the vagina the most important site for orgasm (when compared to women for whom the clitoris was the most important site for orgasm) had more desire for sex with a partner, but not more desire for masturbation.…”
mentioning
confidence: 96%
“…Details on the prevalence of SD of the two groups of respondents were reported elsewhere. 8,13 It is interesting to see that only the wive's Co-occurrence of SD in rural China JTF Lau et al pain during intercourse, but not other categories of wives' SD, was associated with husbands' SD. Further, wives' pain during intercourse was significantly associated with almost all types of husbands' SD (except husbands' pain during intercourse).…”
Section: Discussionmentioning
confidence: 99%
“…A sample of 1300 out of 4100 such women was randomly selected, out of which 1198 women participated in another survey on female SD. 8 A random subsample of 380 women was selected from the 1198 women and their husbands were invited to join this study; 302 husbands (79.5%) hence consented and participated in the study. Four were excluded from the analysis, as they were not sexually active during the past year.…”
Section: Population and Samplingmentioning
confidence: 99%